2018
DOI: 10.1093/bioinformatics/bty680
|View full text |Cite
|
Sign up to set email alerts
|

VisioProt-MS: interactive 2D maps from intact protein mass spectrometry

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Alternatively, it can be adapted and included in more complex workflows. All the information concerning its features, compatibility, and usages can be found in Locard-Paulet et al 17 and on the associated online help (https://masstools.ipbs.fr/visioprothelp.html).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, it can be adapted and included in more complex workflows. All the information concerning its features, compatibility, and usages can be found in Locard-Paulet et al 17 and on the associated online help (https://masstools.ipbs.fr/visioprothelp.html).…”
Section: Discussionmentioning
confidence: 99%
“…For MS traces, raw files were automatically deconvoluted with the rolling window deconvolution software RoWinPro 8 and the proteoform footprints were visualized with VisioProt-MS v2.0. 17 Top-down raw data were analyzed with Proteome Discoverer v2.2 (Thermo Scientific) using the ProSight PD Top-Down Low/High node. Briefly, intact protein spectra were deconvoluted with ReSpect (precursor mass between 20 000 and 30 000 Da and 100 ppm mass tolerance, charge state range between 15 and 35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published study, a new standalone soware called VisioProt-MS was reported, which provides a 2D LC-MS map representation by taking-up LC-MS data of TD studies. 256 Further, VisioProt-MS can take-up data from different types of instrument congurations, e.g., FT-ICR, orbitrap, Q-TOF and therefore, aids in better comparison of the TD LC-MS data. The charge state of the precursor ion as well as of the fragment ions can be determined from the respective isotope peak m/z values, for which high-resolution mass analyzer is essential; in other words, MS/MS spectral data acquisitions must be accomplished in a high-resolution mass analyzer.…”
Section: Tandem Mass Spectrometry (Ms/ms)mentioning
confidence: 99%
“…Ultimately, combining these approaches results in improved confidence in the identification (Ntai et al, 2016). Although there are tools capable of visualizing TDP data, such as VisioProt-MS, which is able to visualize plots of molecular weights of eluting proteins as a function of their retention time (Locard-Paulet et al, 2019;Lesne et al, 2019), there are very few computational tools that combine data from these different strategies. For instance, Proteome Discoverer enables to perform BUP and TDP database searches independently, but does not provide modules to check the number of identified peptides corresponding to an identified proteoform (Scheffler).…”
Section: Introductionmentioning
confidence: 99%